Youth Perspectives on Climate Change : A Comparative Study of Perhentian and Redang Islands - Norhayati, Ab Manaf; Siti Nor Adawiyah Azzahra, Kamaruddin; Dony Adryansyah, Nazaruddin; Akmal, Raffi (Common Ground Research Networks, 2025)
Climate change poses significant threats to island communities. Youths play a crucial role in climate adaptation and mitigation efforts, yet their perspectives and engagement remain understudied in many island settings. This study aims to assess youth awareness, action, and knowledge of climate change on Perhentian and Redang Islands; compare their perspectives; and provide recommendations to enhance youth participation in climate action and adaptation strategies. In total, 148 youths participated in this study using a cross-sectional survey by stratified random sampling. Data were collected through structured questionnaire surveys and analyzed using descriptive and inferential statistical methods. The findings indicate significant differences in awareness, action, and knowledge between the two island communities (p < 0.05). Factors contributing to these differences include the presence of environmental education programs, exposure to conservation projects, the influence of social media, and the integration of traditional ecological knowledge in daily practices. Youths from families involved in eco-tourism or conservation efforts exhibit greater awareness and proactive attitudes toward climate issues. Limited access to environmental education and fewer youth-led initiatives on Perhentian Island contribute to lower engagement levels. This study emphasizes the need of culturally appropriate climate education, digital engagement tactics, and community-based conservation projects for increasing climate awareness and action among island youths. Strengthening partnerships between local governments, educational institutions, and non-governmental organizations (NGOs) can lead to effective youth participation in climate resilience initiatives. This study will help policymakers and conservation practitioners in planning targeted initiatives to promote sustainable development and climate adaptation in vulnerable coastal communities.